Determination of the Dirichlet condition in an electrodynamic problem describing the anyzotropically conductive medium - Vytautas Kleiza; Silvija Sėrikovienė (Lietuvos Matematikos Rinkinys)
The paper deals with the problem of potential determination on a plain domain, using the conformal mapping theory.